Annual review of anthropology / Annual Reviews Inc. - Annual Reviews Inc.; Siegel, Bernard J. (Palo Alto, California : Annual Reviews Inc., 1981)
"The Annual Review of Anthropology covers significant developments in the subfields of anthropology, including archaeology, biological anthropology, linguistics and communicative practices, regional studies and international anthropology, and sociocultural anthropology."
Ethnographic aspects of the world capitalist system Nash, June
Includes bibliographical references and index.
In English.
Keywords: Anthropology -- Periodicals; Physical anthropology; Ethnology; Archaeology; Linguistics